JUAL BELI ONLINE BENTUK MUAMALAH DI MASA MODERN DI TINJAU DALAM HUKUM ISLAM - Muhammad Ibnu Faruk Fauzi (Jurnal ini dipublikasikan oleh Pusat Penelitian dan Pengabdian Publikasi (P3M) STAI Nahdlatul Watan Samawa-licensed under a Creative Commons Attribution-ShareAlike 4.0 International License., 2023)
The use of modern technology (such as computers or mobile phones) as a tool to facilitate buying and selling business activities is a very profitable marketing strategy. In today's digital era, there are many trade transactions through cyberspace (online or via the internet), so that between sellers and buyers are not limited by space and time. This research is a type of library research. The focus of library research is to find various theories, laws, propositions, principles, or ideas that are used to analyze and solve formulated research questions. The nature of this research is descriptive analysis. The results show that in the form of contracts that can be adopted in on-line transactions are bay' al-murabahah and bay' as-salam. An online sale and purchase contract is valid if it has fulfilled the pillars and conditions of sale and purchase, including with the provisions that the goods purchased are halal and have clear specifications, the goods to be purchased are goods that are indeed needed so that they do not cause tabzir, the buyer has the right to return or cancel the sale if the goods purchased are not in accordance with the order, and online buying and selling must be carried out according to the buying and selling scheme